Simulation of 4-coils Magnetic Resonance Coupling for Multiple Receivers Wireless Power Transfer at Various Transmission Distance - Tan S.Y.; Lee H.J.; Lau K.Y.; Ker P.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer software; Efficiency; Energy transfer; Magnetic resonance; Magnetism; distance; Electric and magnetic fields; Magnetic resonance couplings; Multiple coils; resonant; Separation distances; Transmission distances; Wireless power transfer; Inductive power transmission